2016
DOI: 10.3389/fneur.2016.00230
|View full text |Cite
|
Sign up to set email alerts
|

Altered Kinematics of Facial Emotion Expression and Emotion Recognition Deficits Are Unrelated in Parkinson’s Disease

Abstract: BackgroundAltered emotional processing, including reduced emotion facial expression and defective emotion recognition, has been reported in patients with Parkinson’s disease (PD). However, few studies have objectively investigated facial expression abnormalities in PD using neurophysiological techniques. It is not known whether altered facial expression and recognition in PD are related.ObjectiveTo investigate possible deficits in facial emotion expression and emotion recognition and their relationship, if any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 50 publications
2
39
0
1
Order By: Relevance
“…Pearson’s correlation test revealed a relationship between the ability to recognize emotions and the ability to express emotions in both facial and vocal emotion tasks. In a recent kinematic study, Bologna et al 11 did not find any correlation between emotional recognition deficits and altered facial emotion expression kinematics in patients, suggesting that these abnormalities are mediated by two separate pathophysiological mechanisms. The emotional recognition test used in that study was similar to the one used in this study, although the facial emotional expression methods were different.…”
Section: Discussionmentioning
confidence: 91%
“…Pearson’s correlation test revealed a relationship between the ability to recognize emotions and the ability to express emotions in both facial and vocal emotion tasks. In a recent kinematic study, Bologna et al 11 did not find any correlation between emotional recognition deficits and altered facial emotion expression kinematics in patients, suggesting that these abnormalities are mediated by two separate pathophysiological mechanisms. The emotional recognition test used in that study was similar to the one used in this study, although the facial emotional expression methods were different.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a relation between emotion recognition and a lack of automatic mimicry during observation of emotional facial expressions was recently reported ( 20 ). Although one study did not find a significant relation between velocity and amplitude of voluntary facial muscle activation and emotion recognition [note that sample size was small and effect size was not reported ( 21 )], we assume that further examination of the association between emotion recognition deficits and facial motor impairments are valuable. Based on current theories of social cognition, it was assumed that the “neural resonance” in the observer’s motor system that normally facilitates understanding of facial expressions ( 22 ) is disturbed in PD ( 20 ).…”
Section: Introductionmentioning
confidence: 87%
“…Bowers and colleagues used computer vision techniques to quantitatively analyze videos of facial expressions and concluded that PD patients show less and slower voluntary facial movements [25]. Using a 3D optoelectronic system, Bolonga and colleagues assessed voluntarily mimicked facial expressions of emotion [26]. They found a slower velocity and lower amplitude in the PD group compared to controls while mimicking basic emotions.…”
Section: Introductionmentioning
confidence: 99%